SYNTHESIS OF BIODEGRADABLE POLYESTER BASED ON RENEWABLE RESOURCES - Jovanović, Vojislav; Ristić, Ivan; Miletić, Aleksandra; Cakić, Suzana; Tanasić, Jelena; Budinski-Simendić, Jaroslava (Bulletin of Natural Sciences Research, 2019)
Due to the growing problem caused by waste plastics, academia and industry, invest great dials of efforts to solve this problem and enable the sustainability of polymeric materials. One way, which can successfully solve this problem, is certainly the synthesis of new polymeric materials based on renewable raw materials. Therefore, in this paper, synthesis of polyester based on ricinoleic acid (as well as the methyl ester of ricinoleic acid) is presented, in order to obtain the polyol of the desired molar masses. The polymerization of the ricinoleic acid was performed in the presence of diethylene glycol, as an initiator, and titanium isopropoxide, as a catalyst. By analyzing the molar masses of the obtained polyesters, it has been confirmed that the control of the molecular weight of the polyricinoleic acid can be successfully accomplished by the addition of a precisely determined amount of diethylene glycol, thus enabling in this way the synthesis of polyols of desired properties. The molecular structure of the synthesized polyols is confirmed by FTIR and NMR spectroscopy. The analysis of the thermal properties showed that the glass transition temperatures of the synthesized polyols range from -70 to -80ºC, which makes it possible to apply these materials in low-temperature applications. The slight increasment of thermal stability is observed, only with the increasment of molecular weight, which was confirmed by TG analysis. The viscosity measurement results confirmed that as the molar weight of synthesized polyester increases, the viscosity of the samples also increases.
Keywords: Biodegradable polyesters; Renewable resources; Polyricinoleate; Thermal properties